Critical political geographies of slow violence and resistance. (March 2022) - Pain, Rachel; Cahill, Caitlin
Engaging Rob Nixon's conceptualisation of slow violence, this special issue provides a critical framework for how we understand violence relevant to political geography. In this introduction, we highlight three key contributions of the collection that build upon and extend Nixon's framing of slow violence. First, we attend to the spatialities of slow violence, revealing how the politics of disposability and racialised dispossession target particular people and places. Next, we foreground critical feminist and anti-racist perspectives that are largely absent in Nixon's original account. And third, through engaging these approaches, the papers together employ an epistemological shift, uncovering hidden and multi-sited violences that prioritise the accounts of those who experience and are most affected by slow violence.